THE USE OF STUDENT TEAM ACHIEVEMENT DIVISION (STAD) IN IMPROVING WRITING ABILITY AT THE ELEVENTH GRADE OF SMA N 1 NAWANGAN IN ACADEMIC YEAR 2019/2020 - Anton Edi Purnomo; Bambang Harmanto; Niken Reti Indriastuti (Universitas Muhammadiyah Ponorogo, 2019)
Writing is an important language skill because it becomes a means of learning, discovering, developing, and perfecting skills of language. The researcher using the Student Team Achievement Division (STAD) method to improve student writing ability. The aim was to change the classroom situation, so that the students will more interested in learning processes, and it will be easier for them to understand the material especially in writing class. The researcher used classroom action research as the research design. The subject was the eleventh grade MIPA 1 SMA N 1 Nawangan on 2019/2020 lesson year. The class consists of 24 students. Before implementing the research, the researcher made lessons plan, scenario teaching using STAD and prepared instruments, questionnaire, observation, and test. The research was conducted in two cycles. Each cycle consisted of three meetings. The first and second meetings was the implementation STAD method and the third was the test. Based on the result of the observation it showed that the students were more active than previous meeting, the percentage was 67% in cycle one and 88% in cycle two. The result of the questionnaire score was 68.4% in cycle one and 74.2% in cycle two it meant the students were more enjoyed, gave positive response and looked more fun with implementation those method. The result of writing test in cycle one it was known that 14 students or 58% who got score above 70, in cycle two was 100% or all students got score above 70. The result of writing test in cycle two, it showed improvement. The research finding proves that STAD method was successfully in improve writing ability. The researcher suggest that using STAD method in writing skill is a good alternative to teach and learn writing in order to make the learning process become more effective and independent